Breeding seasonality of Tylopoda: Expected patterns in Old World camelids but an exceptional pattern in South American camelids - Nicole Pauli; Marco Roller; Marcus Clauss (PLoS ONE, 2025)
Seasonal breeding is a common adaptation among mammals in seasonal environments, ensuring offspring is born under favourable conditions. As only conception can be controlled but not birth itself, a predictive cue for these favourable conditions is needed (e.g., photoperiodism). Seasonal breeding, however, can also be disadvantageous if there will be time spent waiting until the next breeding season starts. We hypothesized that Old World camelids (OWC; C. bactrianus and C. dromedarius ) exhibit a less pronounced seasonal breeding than South American camelids (SAC; L. glama, L. guanicoe, V. vicuna, V. pacos ), given the higher costs of strict seasonality in OWC due to their gestation length (OWC ~ 13 months, SAC ~ 11 months). Both groups are expected to be long-day breeders, so that births occur in spring. We assessed data on conceptions of Camelidae, both from literature and zoo populations, and included information on latitude of origin and wet season. All camelid species were able to breed year-round, with the domestic forms of SAC being less seasonally restricted. OWC showed tendencies to long-day breeding, whereas SAC unexpectedly showed tendencies to short-day breeding. Patterns of conception peaks of literature and zoo populations were similar, suggesting the (partial) influence of photoperiodism. Further, inter-individual differences, as described for some rodents, cannot be ruled out. The climatic conditions and vegetational growth pattern of the natural habitat of SAC might explain the surprising short-day breeding seasonality. It deviates from the global pattern insofar as the most beneficial environmental conditions occur in autumn.